Niveles de lenguaje oral en niños de 3 años de una institución educativa inicial del Callao - Lino Ramirez, Rosa Violeta (2012)
The research was conducted to determine the level of oral language development in children 3 year of kindergarten school Callao in their dimensions: form, content and use, The sample included 80 children of low socioeconomic level. Were assessed with the oral language tesr revised Navarra (2004), Aguinaga, Armentia, Fraile,Olangua and Uriz , adapted for Metropolitan Lima for Dioses (2006) and adapted for Callao in the dimension form Quezada (2010) . The results show that there is a low level of oral language in the dimensions mentioned.